In Vitro Infection of Trypanosoma cruzi Causes Decrease in Glucose Transporter Protein-1 (GLUT1) Expression in Explants of Human Placental Villi Cultured under Normal and High Glucose Concentrations - Luciana Mezzano; Gastón Repossi; Ricardo E. Fretes; Susana Lin; María José Sartori; Sofía G. Parisi de Fabro (Journal of Tropical Medicine)
Trypanosoma cruzi, the etiologic Chagas' disease agent, induces changes in protein pattern of the human placenta syncytiotrophoblast. The glucose transporter protein-1 (GLUT1) is the primary isoform involved in transplacental glucose transport. We carried out in vitro assays to determine if T. cruzi infection would induce changes in placental GLUT1 protein expression under normal and high concentration of glucose. Using Western blot and immunohistological techniques, GLUT1 expression was determined in normal placental villi cultured under normal or high concentrations of glucose, with or without in vitro T. cruzi infection, for 24 and 48 hours. High glucose media or T. cruzi infection alone reduced GLUT1 expression. A yet more accentuated reduction was observed when infection and high glucose condition took place together. We inform, for the first time, that T. cruzi infection may induce reduction of GLUT1 expression under normal and high glucose concentrations, and this effect is synergic to high glucose concentrations.